2013
DOI: 10.5194/bg-10-1483-2013
|View full text |Cite
|
Sign up to set email alerts
|

Response of <i>Nodularia spumigena</i> to <i>p</i>CO<sub>2</sub> – Part 3: Turnover of phosphorus compounds

Abstract: Abstract. Diazotrophic cyanobacteria form extensive summer blooms in the Baltic Sea driving the surrounding surface waters into phosphate limitation. One of the main bloom-forming species is the heterocystous cyanobacterium Nodularia spumigena. N. spumigena exhibits accelerated uptake of phosphate through the release of the extracellular enzyme alkaline phosphatase whose activity also serves as an indicator of the hydrolysis of dissolved organic phosphorus (DOP). The present study investigated the utilisation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 77 publications
(104 reference statements)
1
22
1
Order By: Relevance
“…Thus, variations and differences in the treatments can be overseen at daily sampling. Unger et al (2013) demonstrated that an accelerated PO 4 uptake by the cyanobacterium Nodularia spumigena under elevated CO 2 incubations could only be observed during the first hours. Thereafter, the differences were balanced and the same level of radiotracer labelling was reached in all treatments.…”
Section: Response Of P-pools and P-uptake To Enhanced Co 2 In The Mesmentioning
confidence: 95%
See 3 more Smart Citations
“…Thus, variations and differences in the treatments can be overseen at daily sampling. Unger et al (2013) demonstrated that an accelerated PO 4 uptake by the cyanobacterium Nodularia spumigena under elevated CO 2 incubations could only be observed during the first hours. Thereafter, the differences were balanced and the same level of radiotracer labelling was reached in all treatments.…”
Section: Response Of P-pools and P-uptake To Enhanced Co 2 In The Mesmentioning
confidence: 95%
“…The final volume was recorded. The dATP concentrations were measured in triplicate using the firefly bioluminescence assay and a Sirius luminometer (Berthold Detection Systems Pforzheim, Germany), as described by Unger et al (2013). Standard concentrations were prepared as described above, using aged Baltic Sea water and six ATP concentrations (adenosine 50-triphosphate disodium salt hydrate, SigmaAldrich, A2383) ranging from 1 to 20 nmol L −1 .…”
Section: Dissolved Atpmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional differentiation of organic and inorganic P requires a big effort which takes much time. It is hardly realizable to measure organic P in its entirety rather its single compounds like DNA and RNA or ATP which have a minor part in the DOP (Unger et al, 2013). Furthermore, when using the molybdenum blue method, labile P components other than DIP, e.g., labile organic P or colloidal bound P, may also be bound to the molybdenum blue complex (Rigler, 1968;Stainton, 1980;Haygarth and Sharpley, 2000;Jarvie et al, 2002).…”
Section: Introductionmentioning
confidence: 99%